Antimicrobial Activity of Sequential Extracts from Leaves of Cassia nodosa Bunch. - Singh, D.; Sharma, R.A.; Sharma, B.; Sharma, S.K.; Sharma, D.; Chandrawat, P.; Sharma, S. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of the sequential extracts (petroleum ether, benzene, acetone, chloroform, ethanol, water etc.) of the leaves of C. nodosa carried out against certain bacteria viz., Staphylococcus aureus, Salmonella typhi, Escherichia coli, Pseudomonas aeroginosa and fungi viz., Aspergillus flavus, A. niger, Fusarium moniliformae and Rhizoctonia bataticola using disc diffusion technique. Present study showed that most of the extracts were effective against all the test microorganisms. The minimum inhibitory concentrations of the extracts of chloroform, benzene, acetone and ethanol were found to be 2 × 104 mg/mL, while the petroleum ether and water showed no inhibition. Present investigation provides scientific basis for the use of the plant extracts in the treatment of fungal and bacterial diseases. It is concluded that the active principles possessing antimicrobial activity may be extracted from the leaves of Cassia nodosa by various organic solvents.